The effect of iron powder particle size to the cracked core defect - a case study on molded inductor (HM72A-12XXX) - Siti Anom , Lehan (2013)
Cracked core defect is a visible fracture or point of separation which appear on the surface of the part, but does not propagate through the entire thickness of the part. In semiconductor industries, it is a challenge to manufacture products that is free of crack defects. The effect of iron powder particle size to the cracked core defect has been studied in this research. This research is conducted at molded inductor section at BI Technologies Corporation Sdn Bhd. The part HM72A-12XXX series has been selected as a case study because it has the highest number of reject with the percentage of 34.1 percent. In order to obtain sample with different average particle size, two samples of iron powder from different supplier has been selected. These two powders are ATMIX11 and TP-18. The size of TP-18 is smaller than ATMIX-11, ranging from 6µm - 8µm while ATMIX-11 is 12µm after the particle size distribution analysis. The surface morphology, roughness and the width of crack are observed from the experimental results. The results show that a larger particle size is better than small particle size because the percentage of crack defect by using ATMIX-11 is lower than TP-18 which is 9.4 percent and 18.1 percent respectively.